Application of eggshell as catalyst for low rank coal gasification: Experimental and kinetic studies. Issue 5 (October 2017) - Fan, Shumin; Xu, Li-Hua; Kang, Tae-Jin; Kim, Hyung-Taek
Abstract: The objective of this research was to study effects of waste eggshells (ES) as a catalyst on the gasification of Indonesian sub-bituminous Komisi Pemilihan Umum (KPU) coal in a fixed-bed reactor under atmospheric pressure at three temperatures (700, 800, and 900 °C). With the ES catalyst, the highest H2 yield of 1.24 mol-/mol-C (64 vol%) was obtained, an 80% increase compared with that of raw coal gasification without catalyst (0.69 mol-/mol-C). In addition, a CO yield of 0.34 mol-/mol-C was obtained, which is 31% higher than that of raw coal gasification (0.26 mol-/mol-C). Compared to raw coal gasification without catalyst, the ES catalytic gasification had higher syngas yield and reactivity. Through comparison, the best model for describing the reactivity of KPU coal with ES catalyst was the RPM (Random pore model) among the three gas–solid reaction models adopted in this research. The RPM could adequately describe the conversion rate, giving an accurate prediction and explanation of the rate change during gasification. Rational kinetic parameters were determined from the RPM, which provided a basis for design and operation of a realistic system. Highlights: The egg shell catalyst improved the yields of useful gases, including hydrogen and carbon monoxide during coal gasification. The ES catalytic gasification had higher syngas yield and reactivity. Compared to raw coal gasification, the ES catalyst reduced the activation energy of gasification.